“A Long Interior Journey” of Kate Brown as Border Crossing: Gender, Age, and Class in Doris Lessing’s “The Summer Before the Dark” - Miroshnychenko, Lilia (Respectus Philologicus, 2017)
The essay collection Doris Lessing: Border Crossings (2009), claims the writer’s persistent impulse to cross borders of all kinds – gender, maternity, class, ideology, geography, etc., and explores the impact it has on Lessing’s novels and autobiography. It therefore offers a new critical and theoretical approach that revises a traditional methodological paradigm of Lessing studies. This article extends the field of exploration by examining the transgressions of borders in the author’s novel of 1973 The Summer Before the Dark. Despite the extensive scholarship on the writer over the last years this novel remains among those which are less explored. However, it is relevant to the new theoretical scheme suggested by the authors of the volume. A central protagonist, Kate Brown, breaks restrictive gender and age codes as she is moving into “the darkness” of her new life order. The controversy of this move is announced in the title of the novel but towards its end the text suggests a transformation that enables the heroine to revise her agency inside and outside the domestic space, at the same time, through a set of narrative techniques and imagery, it problematises such a change.
Keywords: Doris Lessing; Border Crossing; Identity; Gender; Age